E-Healthcare Adoption, User Satisfaction, and Clinical Effectiveness - Ahmed Hamid Saleh,; Ahmed Sabeeh Yousif, (International Journal of Computers and Informatics, 2026)
Background: E-healthcare, telemedicine, and online health platforms are being increasingly employed to facilitate greater access to healthcare services. Nevertheless, there remains a need to generate real-world evidence for e-healthcare utilization, patient satisfaction, and outcomes from diverse geographic regions across the world. Objective: To identify the factors that determine e-healthcare utilization and patient satisfaction, as well as to determine if certain clinical outcomes from e-healthcare utilization are non-inferior to traditional healthcare, a mixed-methods approach was employed across diverse global regions. Methods: A total of 100 patient survey respondents, 167 patients for clinical outcomes, and 7 healthcare provider interviews were conducted over a period of 24 months in North America, Europe, and Asia Pacific. Quantitative methods employed multivariable logistic regression, non-inferiority propensity score matching, and survival analyses. Qualitative methods employed thematic content analysis. Results: Of the total survey respondents (n = 102), the mean age was 48.3 years (SD = 14.2), with a retention rate of 74.2% (n = 76) for 12 months or longer. Determinants for e-healthcare utilization were digital literacy (OR = 2.34; CI = 1.89, 2.91) and convenience (OR = 2.18; CI = 1.76, 2.70). The mean patient satisfaction score was 8.4 (SD = 1.2) out of a possible 10, with a major predictor for satisfaction being trust for the provider (β = 0.62; p < 0.001). Non-inferiority tests for clinical outcomes for e-healthcare utilization compared to traditional healthcare for diabetes, hypertension, and mental health showed non-inferiority for e-healthcare utilization. For diabetes, the differences in HbA1c for e-healthcare compared to traditional healthcare were -0.15% (CI -0.38% to +0.08%) with a non-inferiority margin of -0.5%. Hypertension control was achieved in 95.8% vs. 94.2% (p = 0.002), while improvement in depressive symptoms was by 7.2 vs. 6.8 on the PHQ-9 (p = 0.156). Acute care utilization was reduced by 23% for e-healthcare (38 per 1,000 vs. 49 per 1,000 (p < 0.001)). Three major challenges for e-healthcare utilization were training needs, interoperability, and reimbursement policy.
Keywords: Telemedicine; Digital health; E-Healthcare Adoption; Patient Satisfaction; Mixed methods; Clinical Effectiveness